Science Librarianship at America's Liberal Arts Colleges: Working Librarians Tell Their Stories, 1st edition - Stankus, Tony (Routledge, 2020)
In this book, first published in 1992, science librarians analyse the life and times of small liberal arts college science libraries and the workday life of librarians serving scientists from a main campus library. They describe their efforts to defend expensive science collections in the face of tight budgets, to singlehandedly monitor and select literature in all areas from astronomy through zoology, and to compete with the humanities and social studies for library shelf space.